38. Comparison between Anger and Compton cameras for medical imaging: A Monte Carlo simulation study. (December 2017) - Fontana, M.; Dauvergne, D.; Krimmer, J.; Létang, J.M.; Ley, J.L.; Maxim, V.; Testa, E.
Abstract : Introduction: Single Photon Emission Computed Tomography (SPECT) is at present one of the major techniques for non-invasive diagnostics in nuclear medicine. Almost the whole clinical routine is based on collimated cameras, originally proposed by Anger. Due to the presence of mechanical collimation, detection efficiency and energy acceptance are limited and fixed by the system geometrical features. In order to overcome these limitations, the application of Compton cameras for SPECT is being investigated for several years. Methods: We propose in this study to compare a commercial SPECT-Anger device, the GE Healthcare Infinia system with HEGP collimator, and the Compton camera prototype under development by our collaboration[1], through Monte Carlo simulations (GATE v7.1 and Geant4 9.6 respectively). Given the possible introduction of new radio-emitters at higher energies intrinsically allowed by the Compton camera detection principle, the detectors are exposed to point-like sources at increasing primary gamma energies, from actual isotopes already proposed for nuclear medicine applications. The detector performances are studied in terms of radial event distribution, detection efficiency and final image, obtained by gamma transmission analysis for the Anger system, and with an iterative LM-MLEM algorithm for the Compton reconstruction. Results: Preliminary results show for the Compton camera a detection efficiency increased of a factor greater than an order of magnitude, associated with an enhanced spatial resolution for energies beyond 500 keV. Conclusion: We discuss then the proven advantages of Compton camera application with particular focus on dose delivered to the patient, examination time and spatial uncertainties.